2005
DOI: 10.1002/jgm.705
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival and concomitant gene expression of ribozyme‐transduced CD4+ T‐lymphocytes in HIV‐infected patients

Abstract: The proof of principle results reported here demonstrate safety and feasibility of this type of gene transfer approach. While not specifically tested, T-lymphocytes containing an anti-HIV gene construct may impact on HIV-1 viral load and CD4+ T-lymphocyte count, potentially representing a new therapeutic modality for HIV-1 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 49 publications
(54 reference statements)
2
63
0
2
Order By: Relevance
“…Recent clinical gene transfer studies give reason for optimism that this goal is feasible. 13,14 Transgenes. Many transgenes protect HIV-susceptible cells from HIV infection and/or replication in vitro.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Recent clinical gene transfer studies give reason for optimism that this goal is feasible. 13,14 Transgenes. Many transgenes protect HIV-susceptible cells from HIV infection and/or replication in vitro.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Recent early phase clinical studies report that ex vivo gene delivery to stimulated blood T cells using lentiviral or retroviral vectors, followed by expansion and reinfusion, has so far been safe. 13,14 In most patients percentages of circulating lymphocytes (PBL) carrying the transgene decline, often becoming undetectable by 6 months. However, gene-marked blood cells persist at low levels in some subjects.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Many ribozyme-based strategies for treatment of HIV-1 infection have been developed and show promising antiviral activity in vitro (Hotchkiss et al, 2004;Sarver et al, 1990;Zhou et al, 1994). Three ribozymes directed against HIV-1 tat/vrp (Amado et al, 2004;Macpherson et al, 2005;Mitsuyasu et al, 2009), HIV-1 rev/tat (Michienzi et al, 2003) and the viral U5 leader region (Wong-Staal et al, 1998) have already been tested in separate clinical trials. The gene transfer was proven to be safe in all studies, but none showed significant antiviral efficacy.…”
Section: Antiviral Rnasmentioning
confidence: 99%
“…Robust antiviral effects were documented, particularly in patients with high viral loads. Furthermore, Macpherson et al 77 have reported persistent engraftment of T cells for longer than 4 years after treatment of syngeneic CD4 + T cells with an MLV vector expressing an anti-tat ribozyme. This study was similar to that of reference 75 in that cells were transduced either with an empty vector or a vector expressing an anti-HIV-1 payload.…”
Section: Early Genetic Antivirals In T Cellsmentioning
confidence: 99%